Long-Term Observation of Higher-Order Aberrations and Microdistortions in Bowman’s Layer After Small Incision Lenticule Extraction for the Correcting Myopia With Spherical Equivalent Higher Than −9.0 Diopters - Zhou, Xueyi; Qin, Bing; Han, Tian; Shang, Jianmin; Chen, Zhuoyi; Zhao, Jing; Yao, Peijun; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose To evaluate the outcomes in corneal higher-order aberrations (HOAs) and microdistortions in the Bowman’s layer after femtosecond laser small incision lenticule extraction (SMILE) for correcting extremely high myopia. Methods This prospective study included patients with myopia with spherical equivalent ≥ -9.0 Diopters (D). SMILE was performed in forty eyes of 40 patients. Pentacam was used to evaluate HOAs before and at 1 day, 3 months, 6 months, and 2 years after surgery. Fourier-domain optical coherence tomography was used to evaluate microdistortions at 2 years postoperatively. Thirty-two eyes of 32 patients receiving femtosecond laser-assisted in situ keratomileusis (FS-LASIK) were enrolled as the control group. HOAs were measured before, at 1 day and at least 1 year postoperatively. Results After SMILE, the long-term safety and effectiveness index was 1.25 and 0.85, respectively. Microdistortions were observed in 73.5% of the eyes at 2 years, with an average number of 1.20 ± 1.22 microdistortions and an average width of 287.37 ± 259.00 μm. We detected more microdistortions in the horizontal meridian than in the vertical meridian (p = 0.035). The average number and width of microdistortions were both higher in the central region (≤4 mm) than in the peripheral region (4–8 mm) (both p < 0.001). With the exception of horizontal trefoil in the SMILE group and vertical trefoil in the FS-LASIK group, significant changes over time were observed in all other HOAs (all p < 0.05). Meanwhile, we detected significant increases in the total corneal HOA, spherical aberration (SA), and coma at all time-points after both surgeries (all p < 0.01). Compared with FS-LASIK, SMILE induced less SA (p < 0.001) and more horizontal coma (p = 0.036). In the SMILE group, the HOA, SA, and trefoil were more in the small optical zone (≤6.0 mm) than in the large optical zone (>6.0 mm) (all p < 0.05). The increase in SA and most trefoil correlated with the mean number of central microdistortions number (all p < 0.05). Conclusion For myopia over −9.0D, the microdistortions in the Bowman’s layer were still detectable in most eyes long-term after SMILE. Both SMILE and FS-LASIK induced more HOAs, mainly HOA, SA, and coma. The small optical zone and microdistortions may affect postoperative aberrations.